Distribution and Short‐term Prognostic Value of the 21‐gene recurrence score in African American compared to White American breast cancer patients. Issue 4 (25th April 2019) - Amro, Ali; Chen, Yalei; Barry, Renee; Susick, Laura; Bensenhaver, Jessica; Proctor, Erica; Petersen, Lindsay; Nathanson, S. David; Ali, Haythem; Loutfi, Randa; Chitale, Dhananjay; Simonds, Alyson; et al.
Abstract: We evaluated 328 patients (34.8% African American [AA]; 65.2% White American [WA]) with hormone receptor‐positive, HER2/ neu ‐negative breast cancer. Mean age (60 years); mean tumor size (1.6 and 1.7 cm for AA and WA, respectively) were similar, and mean BMI was higher for AA (33 vs 29.8; P = 0.001). Recurrence score (RS) distribution was similar‐ 8.3% AA and 5.9% WA with high RS (≥31). No significant differences were observed in delivery of chemotherapy stratified by score. With median follow‐up 27.2 months for AA and 33.4 months for WA, distant recurrence occurred in 1.0% and 1.6%, respectively ( P = 1). Our results suggest comparable RS utility in AA and WA patients.